Kyrgyz Republic Public Expenditure Review : Creating Fiscal Space for Inclusive Growth - World Bank (World Bank, Washington, DC, 2021)
This Public Expenditure Review (PER) of the Kyrgyz Republic is part of the programmatic PER, which aims to help the government strengthen macro-fiscal policies and enhance the effectiveness and efficiency of public spending. To this end, this PER builds on progresses made since 2014 PER and identifies further areas for improvement. It also identifies efficiency-enhancing fiscal measures that can help create the much-needed fiscal space to meet the country's competing development needs in addressing human capital and infrastructure gaps. This PER-1 (phase 1 of the PER) focuses on macro-fiscal and overarching public expenditure management and cross-cutting policy issues by examining the country’s: (1) stance of fiscal policy, (2) public expenditure management, (3) tax policy and administration, (4) fiscal and quasi-fiscal operations of state-owned enterprises (SOEs), (5) inter-governmental transfers and subnational finances, and (6) wage bill management. Phase 2 of the PER focused on efficiency and effectiveness issues in health, education, and sustainability of the pension system.